Fine mapping of qBK1.2, a major QTL governing resistance to bakanae disease in rice - Kushwaha, Amar Kant; Ellur, Ranjith Kumar; Maurya, Sarvesh Kumar; Krishnan S., Gopala; Bashyal, Bishnu Maya; Bhowmick, Prolay Kumar; Vinod, K. K.; Bollinedi, Haritha; Singh, Nagendra Kumar; Singh, Ashok Kumar (Frontiers in Plant Science, 2023)
Bakanae disease caused by Fusarium fujikuroi is an emerging disease of rice causing losses in all rice growing regions of the world. A BC 2 F 2 population was developed by backcrossing the recurrent parent Pusa Basmati 1121 (PB1121), with the recombinant inbred line, RIL28 which harbors a major QTL governing resistance to bakanae, qBK1.2. MASS-Array based SNP assays targeting the genomic region of qBK1.2 helped in fine-mapping the QTL to a region of 130kb between the SNP markers rs3164311 and rs3295562 using 24 recombinants. In-silico mining of the fine mapped region identified 11 putative candidate genes with functions related to defense. The expression analysis identified two significantly differentially expressed genes namely, LOC_Os01g06750 and LOC_Os01g06870 between the susceptible genotypes, PB1121 and resistant genotypes, Pusa1342 and R-NIL4. Furthermore, the SNPs identified in LOC_Os01g06750 produced minor substitution of amino acids with no major effect on the resistance related functional motifs. However, LOC_Os01g06870 had 21 amino acid substitutions which led to creation of LRR domain in the resistant genotype Pusa 1342, thereby making it a potential candidate underlying the major Bakanae resistant QTL qBK1.2. The markers used in fine-mapping program are of immense utility in marker assisted breeding for Bakanae resistance in rice.